Simulation of Boron Dose and Irradiation Time in Lung Cancer Treatment with Boron Neutron Capture Therapy (BNCT) Using MCNP-6 - Nita Handayani; Kevin Kautsar Soelistiyono; Fajar Arianto (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2024)
Boron Neutron Capture Therapy (BNCT) is a cancer radiation treatment. This approach employs a boron carrier agent in the form of a chemical that is injected into the body and then travels to the cancer cells. In a lung cancer case study, BNCT treatment simulation was carried out using Monte Carlo N Particle (MCNP) software version 6.2. The goal of this study was to determine the most effective boron concentration and irradiation duration in lung cancer therapy utilizing the BNCT method. The geometry based on a phantom model created by Oak Ridge National Laboratory (ORNL). The simulated cancer geometry, which is placed in the right lung's middle lobe. The skin, ribs, and right lung are among the organs at risk. The skin, ribs, and right lung are among the organs at risk. The neutron source for the simulation is the collimator output from the Kartini Nuclear Reactor's thermal column. In this simulation, the variations in boron concentrations were 40 g/g, 45 g/g, 50 g/g, 55 g/g, and 60 g/g of cancer tissue at 5 g/g intervals. The researchers discovered a link between boron injection concentration and irradiation time, with higher boron injection concentrations resulting in shorter irradiation times. The volume of boron injected determines the effective dose absorbed by healthy tissue surrounding cancer cells. The effective boron concentration for lung cancer therapy is 60 g/g, with deterministic cell killing in the rib marrow and right lung. When utilizing a boron concentration of 60 g/g, the irradiation time is 20.4 minutes. Boron concentrations of 60 g/g are projected to create an effective irradiation time for BNCT-based lung cancer therapy based on the ALARA principle due to their shorter duration when compared to other concentration variations.